The kinesin superfamily handbook : transporter, creator, destroyer - Friel, Claire (Claire T.) (Boca Raton : CRC Press, 2020)
"This book brings together current information on the families that make up the kinesin superfamily of molecular motors in one comprehensive text; an ideal reference for researchers looking to make comparisons between different families, for specific information on a family, or simply for an overview of the kinesin superfamily. Information is clearly structured and grouped according to individual families and organized in a standardized way, allowing the reader to search and retrieve information on this large superfamily of molecular motors and understand how its individual members carry out a diverse variety of cellular functions. Features: The first book dedicated to the entire kinesin superfamily Enables a fuller understanding of this family of proteins which is becoming an increasing focus of research due to its involvement in diseases such as cancer, neuropathies and ciliopathies. Written in a manner accessible to a range of researchers in the life and medical sciences, including biophysicists, biochemists, and medical researchers"--
The kinesin superfamily / Hannah R. Belsham & Claire T. Friel -- The kinesin-1 family / David D. Hackney & Alison E. Twelvetrees -- The kinesin-2 family -- transporters / William O. Hancock -- The kinesin-3 family -- long distance cargo transporters / Nida Siddiqui & Anne Straube -- The kinesin-4 family / Claire T. Friel -- The kinesin-5 family : transporters and creators / Mary Popov, Alina Goldstein-Levitin & Larisa Gheber -- kinesin-6 / Claire T. Freil -- The kinesin-8 family / Tianyang Liu, Alejandro Pena, Fiona Shilliday & Carolyn A. Moores -- The kinesin-13 family -- specialist destroyers / Julie P. Welburn & Claire T. Friel -- The kinesin-14 family / Marcus Braun, Stefan Diez & Zdenek Lansky -- The kinesin-15 family / Hauke Drechsler, Jaspreet Singh Grewal & Andrew D. McAnish -- The kinesin-16 family / Hanan M. Alghamdi & Claire T. Freil -- Other kinesin Families / Claire T. Friel -- Summary and Future Perspectives / Claire T. Friel.
OCLC-licensed vendor bibliographic record.
Keywords: Kinesin; MEDICAL / Biochemistry; SCIENCE / Life Sciences / Cytology; SCIENCE / Physics